Integrating vermicompost, black soldier fly, and inorganic fertilizers enhances corn growth and yield - Riri Dayang Sari Risman; Chutima Nonkhonman; Kiriya Sungthongwises (Heliyon)
To achieve good agricultural practices and maximize the economic yield of corn, farmers should reduce the use of inorganic fertilizers. A field experiment was conducted in the Chonnabot district, Khon Kaen province, Thailand, during the 2022 and 2023 growing seasons. The aim was to assess the impact of different organic fertilizers and their combinations on the growth and yield of commercial sweet corn (Zea mays L. saccharata) and waxy corn (Zea mays L. var. ceratina) hybrids. The results showed that sweet corn had significantly higher ear fresh weight, protein, fat, and fiber content compared to waxy corn, with values of 7,529.20 kg ha−1, 14.48 %, 4.74 %, and 1.30 %, respectively. Two treatments, F4 (190.63 kg N ha−1 + 46.88 kg P ha−1 + 46.88 kg K ha−1) and F3 (6,250 kg ha−1 of black soldier fly (BSF) + 95.31 kg N ha−1 + 23.44 kg P ha−1 + 23.44 kg K ha−1) resulted in the highest ear fresh weight, with 6,569.90 and 6,275.40 kg ha−1, respectively. In contrast, F4 showed higher protein (12.04 %), fat (4.62 %), and fiber content (0.91 %) than F3. Significant improvements were observed in SPAD value, biomass, and yield parameters. Corn plants treated with a combination of vermicompost, BSF, and inorganic fertilizer showed higher ear length, ear diameter, ear fresh weight, and dry biomass than control plants (no fertilizer management, F1). The F1 treatment led to higher carbohydrate content in both corn cultivars tested, with a notable impact on pink waxy corn (82.06 %). Our findings suggest that using a combination of BSF and inorganic fertilizers is promising for reducing the use of inorganic fertilizers and providing the highest net income among the three fresh corn cultivars. Pink waxy corn showed greater adaptability under low soil fertility conditions owing to better yield components than purple waxy corn when evaluated without fertilizers.